Performance analysis of non-exhaustive wireless sensor networks based on queueing theory. (21st January 2020) - Cao, Jian; Ma, Zhanyou; Guo, Shanshan; Yu, Xiangran
An operation mechanism of wireless sensor networks with non-exhaustive service, multiple adaptive sleep and wake-up strategies is presented on the basis of the queueing theory. The operation mechanism is proposed to dominate the workload of the necessary topology maintenance and reduce the energy consumption. The wireless sensor networks are modelled as a complex discrete-time queueing system. We derive the probability generating functions of the number of the data packets, the access delay, and we obtain the expressions of the mean number of the data packets, the mean response time, the utilisation rate and the throughput, etc. The sensitivity analyses of the performance measures are presented by the numerical experiments. Furthermore, the mathematical analyses are made on the energy consumption. Nash equilibrium and the social optimisation strategies are analysed in detail on the utility by using game theory.